(untitled) (Heritage, 2022)
Frequent and major amendments to the Criminal Code have resulted in many negative effects in Serbian criminal law. One of the consequences of these changes and additions is the adoption of such a crime, which was then "expressly" replaced by the same in just a few months. It is difficult to say whether the original solution was so bad that it had to be replaced immediately, or whether the legislator came up with a new (better) solution that would stop violent behavior at sports events and public gatherings. However, this new legal solution will certainly not achieve what the legislator wanted, which, among other things, in many ways devalues ​​expectations in the already shaky authority of the criminal legislation of Serbia. Without doubting the sincere intentions of the legislator, this crime had to be in the legislative-technical sense, but also in the essential, much better done, as the authors point out, as well as the "pains" of the current legal solution.